GAYA KEPEMIMPINAN, KOMPENSASI DAN PRESTASI ATLET - Seno Andri, Syarkasi Ahmady, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Leadership Style, Compensation and Athlete Achievement. This study aims to analyze the influence of leadership style and compensation on Athlete Achievements in the KONI Riau Province. The method used is descriptive and quantitative methods; The sample is 146 KONI achievers. Technique of collecting questionnaire data, observation and interviews. The types and sources of data used are primary and secondary data. The results of the research that has been done, the conclusions are partially known that the leadership style variables have a significant effect on the achievement of the Riau Province KONI athletes. It is known that the existence of a good leadership style for athletes can increase the athlete’s achievement because leadership style can shape the athlete’s personality better. Partially it is known that compensation variables have a positive and significant effect on the achievement of the Riau Province KONI athletes. This is known if the athlete is compensated according to the achievement and the target will certainly improve the athlete’s performance and vice versa. Simultaneously it is known together that the leadership and compensation style variables have a positive and significant effect on the achievement of the Riau Province KONI athletes, this is indicated by the percentage of 58.3% while the remaining 41.7% is an indication of other factors that can improve athletes’ achievement but not examined in this study. With leadership style and compensation, it will increase the athlete’s ability and will have an impact on improving the athlete’s performance.